2022
DOI: 10.1021/acs.nanolett.2c00724
|View full text |Cite
|
Sign up to set email alerts
|

Single Small Extracellular Vesicle (sEV) Quantification by Upconversion Nanoparticles

Abstract: Cancer-derived small extracellular vesicles (sEVs) are potential circulating biomarkers in liquid biopsies. However, their small sizes, low abundance, and heterogeneity in molecular makeups pose major technical challenges for detecting and characterizing them quantitatively. Here, we demonstrate a single-sEV enumeration platform using lanthanide-doped upconversion nanoparticles (UCNPs). Taking advantage of the unique optical properties of UCNPs and the background-eliminating property of total internal reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…As a bioimaging probe, upconverting nanoparticles (UCNPs) have been widely employed because of their various advantages, including high photostability without photobleaching or photoblinking that facilitates long-term tracking, uniform size and intensity, low cytotoxicity owing to near-infrared (NIR) excitation, no autofluorescence because of large anti-Stokes shift, and multiplexed emission with different activator doping under a single light source. [9][10][11][12][13][14][15][16][17][18] UCNPs functionalized with poly(ethylene glycol) (PEG), which are photostable for tens of hours, 19 can be internalized into a cell through endocytosis and moved in a vesicle as a cargo along the microtubule by motor proteins. 13 Additionally, the cellular interaction of the PEGylated UCNPs, including endocytosis, intracellular transport, and exocytosis was reported in living HeLa cells.…”
Section: Introductionmentioning
confidence: 99%
“…As a bioimaging probe, upconverting nanoparticles (UCNPs) have been widely employed because of their various advantages, including high photostability without photobleaching or photoblinking that facilitates long-term tracking, uniform size and intensity, low cytotoxicity owing to near-infrared (NIR) excitation, no autofluorescence because of large anti-Stokes shift, and multiplexed emission with different activator doping under a single light source. [9][10][11][12][13][14][15][16][17][18] UCNPs functionalized with poly(ethylene glycol) (PEG), which are photostable for tens of hours, 19 can be internalized into a cell through endocytosis and moved in a vesicle as a cargo along the microtubule by motor proteins. 13 Additionally, the cellular interaction of the PEGylated UCNPs, including endocytosis, intracellular transport, and exocytosis was reported in living HeLa cells.…”
Section: Introductionmentioning
confidence: 99%
“…Other superior advantages using UCNPs in nanoscopy include: (1) their non-photobleaching and non-blinking properties, (2) the single-molecule sensitivity achieved by their intense brightness due to the high concentration of tens of thousands of lanthanide ions being doped within each nanocrystal, and (3) the negligible background level in detecting the anti-Stokes shift emissions under the near infrared excitation. Our recent work [29] using UCNPs further achieved the ultra-sensitivity in quantitative detection of sEVs, which recorded a limit of detection 1.8 × 10 6 EVs/mL, nearly 3 orders of magnitude lower than the standard enzymelinked immunosorbent assay (ELISA).…”
Section: Introductionmentioning
confidence: 99%
“…39 However, some of the cases reported that apoptosis occurred at a high cellular dose of UCNPs. [15][16][17][18] Based on the previous studies, [40][41][42] UCNPs come into contact with human tissues and cells, which can trigger inflammatory reactions that might cause cellular damage. Therefore, before applying UCNPs to clinical application, interactions between the UCNPs and human immune cells, and their biocompatibility must be studied at the single-cell level with heterogeneous systems.…”
Section: Cell-associated Ucnps and Cytotoxicitymentioning
confidence: 99%